2000
DOI: 10.1093/oxfordjournals.aje.a010131
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Correct Treatment of Children with Fever Seen at Outpatient Health Facillities in the Central African Republic

Abstract: To identify factors associated with improved performance of health care workers who treat ill children in developing countries, the authors analyzed a sample of consultations of children with malaria (defined as any fever) from a national health facility survey conducted in the Central African Republic from December 1995 to January 1996. Twenty-eight health care workers and 204 children were studied. A univariate analysis revealed the following significant predictors of correct treatment, as defined by the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
3
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 7 publications
2
52
3
3
Order By: Relevance
“…15 Emphasizing rational drug use and improved provider-client communication during pre-service training, as well as on-site refresher training using opinion leaders or district-level staff and supportive supervision, may be more effective methods for improving the case management of malaria in the formal sector. 11 A series of cross-sectional studies of health worker performance generally found that reported experience of in-service training was not significantly associated with correct treatment of uncomplicated malaria [52][53][54] ; in one of the studies, in-service training was associated with appropriate malaria case management, but only when combined with other interventions such as job aides and frequent supervision. 55 Similar mixed findings were reported by a wider review of (non-malaria-specific) interventions to improve health-worker performance.…”
Section: Discussionmentioning
confidence: 99%
“…15 Emphasizing rational drug use and improved provider-client communication during pre-service training, as well as on-site refresher training using opinion leaders or district-level staff and supportive supervision, may be more effective methods for improving the case management of malaria in the formal sector. 11 A series of cross-sectional studies of health worker performance generally found that reported experience of in-service training was not significantly associated with correct treatment of uncomplicated malaria [52][53][54] ; in one of the studies, in-service training was associated with appropriate malaria case management, but only when combined with other interventions such as job aides and frequent supervision. 55 Similar mixed findings were reported by a wider review of (non-malaria-specific) interventions to improve health-worker performance.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of effective case management with ACT faces a number of challenges, notably complex ordering and financing procedures, the need to train health workers and provide clear guidelines for their use, and their introduction into weak health systems commonly characterized by suboptimal drug management and clinical practices [70,71] . Therefore, despite being promising, new ACT drugs might not reach patients who need them and if they do, the challenge remains to ensure adequate clinical practices.…”
Section: Challenges In Implementation Of Act For Uncomplicated Pediatmentioning
confidence: 99%
“…Modifications de la mise en oeuvre du traitement par PTA du paludisme pédiatrique non compliqué La mise en oeuvre d'une prise en charge efficace au cas par cas au moyen d'une PTA se heurte à un certain nombre de difficultés (notamment méthodes complexes de commande et de financement, nécessité de la formation des travailleurs de santé et de la fourniture d'instructions claires sur l'emploi de ces produits et introduction de ces derniers dans des systèmes de santé peu efficaces se caractérisant fréquemment par un aspect non optimal des pratiques cliniques et de la gestion des médi-caments [70,71] ). De ce fait, malgré leurs aspects prometteurs, les nouveaux traitements par PTA pourraient ne pas parvenir aux patients qui en ont besoin et, s'ils leur parviennent, la difficulté persistante consiste à assurer des pratiques cliniques adéquates.…”
Section: Traitement Du Paludisme Pédiatriqueunclassified